1999
DOI: 10.1139/g99-016
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of puffing activity in the salivary gland polytene chromosomes of the medflyCeratitis capitata, during larval and prepupal development

Abstract: The patterns of puffing activity in the salivary gland polytene chromosomes have been studied during the late larval and prepupal stages of the medfly Ceratitis capitata. A total of 128 loci, with significant changes in puffing activity during this developmental period, were assigned to the five autosomes of the medfly. Two waves of puffing activity were observed, the first during the late larval stage and the second during the prepupal development. Overall puffing activity can be divided into four groups, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…This strain has been maintained in our laboratory for more than 25 years under standard conditions (25 ± 1°C, 40-50% relative humidity and 12 h light:12 h dark photoperiod) as previously described (Mintzas et al, 1983). Precise staging of the medfly cultures was obtained according to a procedure described previously (Gariou-Papalexiou et al, 1999). Following this procedure, the embryonic, larval, and prepupal stages last 49 ± 1, 150 ± 2, and 40 ± 2 h, respectively, while the pupal stage lasts about 8 days.…”
Section: Animals and Developmental Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain has been maintained in our laboratory for more than 25 years under standard conditions (25 ± 1°C, 40-50% relative humidity and 12 h light:12 h dark photoperiod) as previously described (Mintzas et al, 1983). Precise staging of the medfly cultures was obtained according to a procedure described previously (Gariou-Papalexiou et al, 1999). Following this procedure, the embryonic, larval, and prepupal stages last 49 ± 1, 150 ± 2, and 40 ± 2 h, respectively, while the pupal stage lasts about 8 days.…”
Section: Animals and Developmental Stagingmentioning
confidence: 99%
“…The numbers indicate the age of each developmental stage in hours. J represents the stage during which the larvae jump off the food and occurs 6 h before white puparium formation (WP) (Gariou-Papalexiou et al, 1999). Ethidium bromide staining of rRNA is showing under the Northern blots as a control for even RNA loading.…”
Section: Archives Of Insect Biochemistry and Physiology March 2008mentioning
confidence: 99%
“…This strain has been maintained in our laboratory for more than 30 years under standard conditions (25 ± 1°C, 40-50% relative humidity and 12 h light:12 h dark photoperiod) as previously described (Mintzas et al, 1983). Precise staging of the medfly cultures was obtained according to a procedure described previously (Gariou-Papalexiou et al, 1999). Following this procedure, the embryonic, larval, and prepupal stages last 49 ± 1, 151 ± 2, and 40 h, respectively while the pupal stage lasts about 8 days.…”
Section: Animals and Developmental Stagingmentioning
confidence: 99%
“…This higher dipteran species has a similar life cycle to D. melanogaster and presents several important advantages for studying 20E regulation. It has well characterized salivary gland polytene chromosomes (Zacharopoulou, 1990) and can be staged precisely during the last hours of larval development because of the jumping event, which takes place about 6 h before puparium formation and coincides with the onset of the first 20E induced puffing cycle (Gariou‐Papalexiou et al ., 1999). Furthermore, C. capitata is the best‐studied fruit fly species of economic importance at the genetic and molecular levels.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies we have determined the puffing patterns of 128 loci in the salivary gland polytene chromosomes during medfly metamorphosis and demonstrated that 20E regulates the activity of most of these puffs (Gariou‐Papalexiou et al ., 1999, 2001). We also have cloned and characterized a medfly ecdysone receptor (CcEcR), the homologue of the Drosophila EcR‐B1 isoform (Verras et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%